Ethnomedicinal Plants Used by the Tribal Communities of West Champaran District of Bihar, India - Singh, H; Mishra, M; Dhole, P A (Plantae Scientia, 2020)
The present paper deals with 67 ethnomedicinal plant species belonging to 61 genera and 36 families used for prevention and treatment of various diseases by the tribal and indigenous non-tribal communities of West Champaran district of Bihar. This first-hand ethnomedicinal information was collected directly from a field survey of 108 remote tribal villages and forest areas of the district. Among them family Leguminosae is represented by maximum number of plants (9 species) followed by Lamiaceae (7 species). Habit-wise analysis revealed that herbs are dominated with 23 species followed by trees. These plant species are arranged in alphabetical order followed by family, habit, local name(s), locality (ies), field number (s) along with a method of preparation and mode of ethnomedicinal uses in detail. After comparison and cross checking of collected uses with relevant standarad literatures, it is revealed that 11 ethnomedicinal uses of plants (marked by *) have not recorded earlier.